Modelling the intention to adopt cloud computing software as-a-service among IT professionals in Iraqi public organisations - Alsharifi, Hiba Jasim Hadi (2022)
Cloud Computing Software as a Service (CC-SaaS) is a distribution model established to provide IT services over the Internet in a convenient on-demand network access. CC-SaaS potentially offers significant opportunities for public organisations to enhance their governmental services without incurring the costs or the management concerns. However, the adoption level of CC-SaaS among governmental organisations is still not satisfactory, and not fully explored in unstable developing countries like Iraq. Along with the absence of an adoption model that clarify the influencing factors affecting the adoption of CC-SaaS among unstable countries like Iraq. Thus, there is a need to investigate and model the factors that may influencing the Iraqi public organisation's decision regarding the adoption of CC-SaaS. Drawing from Technology, organisation and environment (TOE), Diffusion of Innovations (DOI), and Human, Organisation, and Technology (HOT) theories, this study aims to model the intention to adopt CC-SaaS among Iraqi public organisation. A quantitative research paradigm was used in this study, 450 questionnaires were randomly distributed to IT professionals working in six randomly selected ministries. Out of this number, only 301 questionnaires were considered as usable and were analysed using PLS-SEM. Subsequently, the results show that technological, organisational, environmental, and human factors have a statistically significant relationship with CC-SaaS adoption, whereas external support and compliance with regulation was not significant. Further, the result also confirmed the positive mediating role of trust and the moderating effect of IT experience. Additionally, the findings contributed to the body of knowledge by proposing a multi-dimensional model to determine CC-SaaS adoption within public organisation. Further, CC-SaaS adoption strategy was developed based on the final model to guide the policymakers’ decision when moving forward in the adoption process by identifying the constraints that may impede the adoption of CC-SaaS.